Longitudinal profiles of late phonological development in children with Williams syndrome - Martínez, Verónica; Pérez, Vanesa; Antón, María Aránzazu; Miranda, Manuela; Vergara, Patricio (Frontiers in Communication, 2024)
Williams syndrome (WS) is a genetic neurodevelopmental disorder characterized by language skills above what is expected considering non-verbal intelligence. Research on phonological development is scarce, with many studies focusing on grammar in children and adolescents. Our previous study transversally explored the profiles of late phonological development in Spanish-speaking WS children, adolescents, and adults, while our objective is to longitudinally determine these profiles for WS children based on error indexes in spontaneous speech. Participants were seven WS children (aged 3;7-8;2), engaging in two spontaneous conversations within a six-month interval. They were compared cross-sectionally with 240 typically developing (TD) children aged 3-6 years, divided into six groups. All speech samples were transcribed and analyzed with the CLAN software package of the CHILDES Project. Phonological profiles were established on the basis of phonological error indexes obtained dividing absolute frequency of errors by the total number of words produced. WS children showed a mean reduction of more than 25% in the absolute frequency of phonological errors after six months. As for the comparison with the normative groups, their error index was consistent with the stage of expansion in TD, however, after six months, this was consistent with the stage of stabilization. This atypical acceleration in phonological development could be related to lexical growth in the context of relative preservation of phonological memory. Furthermore, the trajectories of late phonological development in WS children might not be linear, as postulated by neuroconstructivist models, suggesting the need for intervention approaches specifically adapted to WS children’s phonological profiles.